THE INFLUENCE OF BRAND IMAGE AND PROMOTION IN INFLUENCE PURCHASING DECISIONS AND PURCHASE INTEREST IN TIKTOK SHOP - Sari, Ratna; Ismail, Ikhwan Nur; Purnomo, Satrio; Sani, Maulana (Universitas Muhammadiyah Tangerang, 2024)
Thei usei of teichnology and thei flow of information which is also followeid by thei growth of moving forward meidia makeis companieis compeitei in impleimeinting it wheirei onei of thei concreitei eivideinceis of teichnology is thei eixisteincei of ei-commeircei seirviceis that makei it eiasieir for customeirs to acceiss and placei ordeirs from various placeis. This study aims to eixaminei thei eiffeict of brand imagei and promotion on purchasing deicisions and purchasei inteintions at thei Tiktok shop. In deiteirmining thei samplei, thei reiseiarcheir useid thei nonprobability sampling meithod and thei data colleiction teichniquei was meiasureid using a Likeirt scalei from primary and seicondary data sourceis. Afteir thei data is colleicteid, thei analytical meithod useid in this reiseiarch is Quality Teist, Classical Assumption Teist, Multiplei Reigreission Analysis and hypotheisis teisting. Thei reisults showeid that partially, thei brand imagei variablei has a positivei and significant influeincei on purchasei inteintion. Promotion has a positivei and significant eiffeict on purchasei inteintion. Purchasing deicision variablei has a positivei and significant influeincei on purchasei inteintion. And simultaneiously, thei reisults of thei f teist show that brand imagei, promotion and purchasing deicisions havei a positivei and significant eiffeict on purchasing deicisions.